2006
DOI: 10.1093/humrep/del027
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and quantification of mRNA transcripts in ejaculated spermatozoa of fertile men by serial analysis of gene expression

Abstract: A SAGE analysis of ejaculate from fertile men has revealed a large number of transcripts, which occur in steady frequencies and probably have important roles in spermatogenesis and fertilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 21 publications
1
67
1
Order By: Relevance
“…The various transcripts that are present in spermatozoa and affect different metabolic pathways or functions raise many questions about the complexity of spermatogenesis and the significance of the transcripts that are generated. We are currently witnessing the emergence of a myriad of diverse transcripts identified using different transcript profiling platforms (Mao et al 2004, Dadoune et al 2005, Zhang et al 2006, Zhao et al 2006, Gilbert et al 2007, Lalancette et al 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…The various transcripts that are present in spermatozoa and affect different metabolic pathways or functions raise many questions about the complexity of spermatogenesis and the significance of the transcripts that are generated. We are currently witnessing the emergence of a myriad of diverse transcripts identified using different transcript profiling platforms (Mao et al 2004, Dadoune et al 2005, Zhang et al 2006, Zhao et al 2006, Gilbert et al 2007, Lalancette et al 2008b.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence suggests that a complex specific mRNA population is retained in freshly ejaculated spermatozoa of several species [1][2][3][4]. In addition, some spermatozoa mRNAs are transferred into the oocyte during fertilization, and remain stable until the activation of the embryonic genome [5].…”
mentioning
confidence: 99%
“…Both have concluded that the mRNA species present within sperm must be either from past events; the gene expression of spermatozogenesis, or for providing the zygote with unique suite of paternal mRNAs. [14][15][16][17] In contrast to transcriptomics, the use of proteomics in sperm biology plays a unique, and arguably, pivotal role unseen in any other tissue/cell type beside blood. However, unlike blood, two important parameters make sperm cell an outstanding candidate for proteomic analysis.…”
Section: The Most Profound Statements Are Often Spoken In Silencementioning
confidence: 99%